Ardisia patentiradiosa (Primulaceae), a new species from southern Vietnam - Nuraliev, Maxim S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Hu, Chi-Ming (Phytotaxa, 2021)
Ardisia patentiradiosa C.M. Hu & Nuraliev (Primulaceae) collected from montane forest of Gia Lai Province, Vietnam, is described and illustrated. Its distinguishing characters from its closest relatives, Ardisia gracilenta C.M. Hu & J.E. Vidal and A. pitardii C.M. Hu & J.E. Vidal, are discussed.